The Influence Of Digital Marketing And Product Variety On Purchase Decisions In Bengkulu City Mode Stores - Lola Vitaloka; Neri Susanti; Tito irwanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The purpose of this study was to determine the effect of digital marketing and product variety on purchasing decisions at Juragan Fashion Shop in Bengkulu City. The sample in this study is 100 consumers who shop at Juragan Fashion Shop in Bengkulu City. Data collection using a questionnaire and the analysis method used is multiple linear regression, test of determination and hypothesis testing.The results of multiple linear regression calculations obtained the multiple linear regression equation Y = 5.995 + 0.355X1 + 0.353X2. The coefficient of determination of the R square value is 0.521. This means that X1 (Digital marketing) and X2 (product variety) affect the purchase decision (Y) by 52.1% while the remaining 47.9% is influenced by other variables not examined in this study. The results of the F test show that the significance is 0.000 0.05. Because the significance level is below 0.05, it indicates that together X1 (digital marketing) and X2 (product variety) have a positive and significant effect together on purchasing decisions (Y). Digital marketing has a positive and significant influence on purchasing decisions, product variety has a positive and significant impact on purchasing decisions because the significant value is smaller than 0.05.